Normalized representation of spin valve resistance value by the hyperbolic metric - Penin Alexandru (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2020)
Magnetoresistive sensors for measuring the magnetic field strength in a wide range up to saturation are considered. Normalized or relative expressions are introduced to change the resistance of the sensor to evaluate the qualitative characteristics of the mode, increase the informativity of the mode, and provide the possibility of comparing different sensors. Magnetoresistors are characterized by three characteristic values (minimum, nominal, and maximum). Therefore, the proposed relative expressions include these characteristic values. To justify these expressions, a hyperbolic straight line geometry and a cross ratio of four points are used. The results are of interdisciplinary interest in view of similarity of characteristics of sensors of different physical nature.Se analizează utilizarea senzorilor magnetorezistivi pentru măsurarea intensității câmpului magnetic într-un interval larg până la saturație. Pentru a modifica rezistența senzorului, a evalua caracteristicile calitative ale regimulului, a spori informativitatea acestuia și a oferi posibilitatea de a compara diferiți senzori sunt introduse expresii normalizate sau relative. Magnetorezistoarele sunt caracterizate de trei valori specifice (minimă, nominală și maximă). De aceea, expresiile relative propuse includ aceste valori caracteristice. Pentru a justifica aceste expresii, se utilizează geometria hiperbolică a liniei drepte și raportul transversal a patru puncte. Rezultatele obținute prezintă un interes interdisciplinar, având în vedere similitudinea caracteristicilor senzorilor de natură fizică diferită.